A general pattern of health erosion in the United States? An examination of self-reported health status from 1997 - 2018 - Alexis R. Santos-Lozada, Ph.D (Elsevier, 2022)
Purpose: Recent research has found a general pattern of health erosion in self-assessed pain and allostatic load among adults in the United States (US). It remains to be determined if self-reported health status, hereafter SRH, also follows this pattern. The aim of this study was to examine whether a general pattern of health erosion is found in SRH among adults in the United States (US). Methods: Data from the National Health Interview Survey 1997-2018 were used to study sex, educational attainment, and racial/ethnic patterns in SRH by age, period and cohort among adults in the US. The analytic sample consisted of respondents aged 18 years or older at the moment of interview with valid information in the age, sex, education, race/ethnicity and health status question (n = 669,501). Estimates for the percent population reporting poor/fair health were produced by age, period and cohort to study trends in health status by sex, educational attainment and race/ethnicity. All estimates were weighted to account for complex survey design. Results: No discernible pattern of health erosion, or improvement, is observed in the age, period or cohort analyses of the percent of the population reporting poor/fair SRH by sex, educational attainment or race/ethnicity. Conclusions: The analysis indicates that self-reported health does not follows the general pattern of health erosion found in self-assessed pain and allostatic load in the US. The percent of the population reporting poor/fair health status has remained relatively stable between 1997 and 2018. Further research is required to determine whether self-reported health is an appropriate metric to track population health in the US.